A method to obtain rapid zoosporogenesis of Pythium insidiosum - Mendoza, Leonel (1988)
Nine strains of Pythium insidiosum the etiologic agent of pythiosis, were inoculated on 2% water agar plus grass blades and then incubated one day at 25°C, 35°C and 37°C. Sporangium and secondary biflagellate-type zoosporas from the parasitized grass blades were noticed in induction medium after one hour of incubation at 35 °C and 37 °C. The number of sporangia and zoospores were lower at 25 °C, than 35 °C and 37 °C. Increasing the days of incubation of the parasitized grass blades resulted in the increase in the time of incubation in the induction medium. Corn meal agar, Schmitthenner medium and Sabouraud dextrose agar were also tested but the sporangium and zoosporas were always observed after five hours of incubation in induction medium. © 1988 Kluwer Academic Publishers.